High-temperature defect recovery in self-ion irradiated W-5 wt% Ta. (January 2019) - Yi, Xiaoou; Arakawa, Kazuto; Du, Yufeng; Ferroni, Francesco; Han, Wentuo; Liu, Pingping; Wan, Farong
Highlights: The high-temperature recovery of self-ion induced radiation defects in W-5 wt% Ta has been studied. After annealing at 1200 °C for 15 min, the damage microstructure (500 °C, 1.2 dpa) evolved from a random distribution of small loops to a mixture of large loops (b  = ½<111>, interstitial nature), dislocation lines and voids. Ta effectively pins the motion of interstitial type defects, but exhibits subtle impact on the evolution of voids. Defect recovery at high temperature differs between self-ion and proton irradiated W-5Ta. Abstract: A study of high-temperature defect recovery has been carried out for W-5 wt% Ta alloy, irradiated with 2 MeV W + ions at 500 °C, up to 1.2 dpa. After post-irradiation annealing at 1200 °C for 15 min, the damage microstructure evolved from a random distribution of small loops to a mixture of large loops, dislocation lines and voids. The average size of loops increased by a factor of ∼4, up to 17.7 nm, whereas the number density dropped by an order of magnitude, to ∼5.3 × 10 21  m −3 . Only loops with b  = ½<111> were observed and they were identified to be exclusively interstitial type. This is in sharp contrast with the presence of ∼25% vacancy type ½<111> loops in the as-irradiated condition. Voids were formed as a result of accelerated vacancy/vacancy-cluster migration at 1200 °C, achieving an average size of ∼2.5 nm and a high density of ∼5.1 × 10 22  m −3 . The role of tantalum is discussed. Furthermore, the high-temperature defect recovery in W-5Ta after self-ion (this work) and proton irradiations (Ipatova et al., 2017) are compared, based on which the possible influence of hydrogen upon defect evolution is discussed.